2023
DOI: 10.1097/shk.0000000000002101
|View full text |Cite
|
Sign up to set email alerts
|

Hemin Attenuated LPS-Induced Acute Lung Injury in Mice via Protecting Pulmonary Epithelial Barrier and Regulating Ho-1/Nlrp3-Mediated Pyroptosis

Abstract: Pulmonary epithelial barrier injury contributes to acute lung injury, accelerating exudate formation, and resulting alveolar edema. Heme oxygenase-1 (HO-1) plays an important role in ameliorating the pathological symptoms of acute lung injury (ALI). Using an ALI mouse model induced by LPS inhalation, the present study explored the potential molecular regulatory effect of hemin (a potent HO-1 inducer) against ALI epithelial damage. Lipopolysaccharide challenge triggered dysfunction of the alveolar epithelial ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…ALI is normally caused by several pathological conditions, namely sepsis, pneumonia, multiple traumas, pulmonary contusion, or aspiration of dangerous gas [51]. Regarding its pathogenesis, ALI is characterized by neutrophil infiltration, accumulation of inflammatory mediators, and hyaline membrane formation [31,51,81].…”
Section: Animal-related Parameters 421 Disease Animal Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…ALI is normally caused by several pathological conditions, namely sepsis, pneumonia, multiple traumas, pulmonary contusion, or aspiration of dangerous gas [51]. Regarding its pathogenesis, ALI is characterized by neutrophil infiltration, accumulation of inflammatory mediators, and hyaline membrane formation [31,51,81].…”
Section: Animal-related Parameters 421 Disease Animal Modelmentioning
confidence: 99%
“…ALI is normally caused by several pathological conditions, namely sepsis, pneumonia, multiple traumas, pulmonary contusion, or aspiration of dangerous gas [51]. Regarding its pathogenesis, ALI is characterized by neutrophil infiltration, accumulation of inflammatory mediators, and hyaline membrane formation [31,51,81]. This disorder is recognized as a major concern worldwide since it presents a high rate of mortality and the underlying mechanisms are not fully understood yet [31,51].…”
Section: Animal-related Parameters 421 Disease Animal Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the high morbidity and mortality, it has become a major burden of public health worldwide (2). Studies have shown that acute lung injury (ALI) is the most common complication of sepsis (3,4), and about 25% to 50% of sepsis patients may occur ALI, which is the main cause of ALI (5)(6)(7). Sepsis-associated ALI (SA-ALI) is characterized by pulmonary edema and inflammatory response (8).…”
Section: Introductionmentioning
confidence: 99%